Proteus Syndrome - Handa Sanjeev; Sahoo Bijaylaxmi; Kumar Bhushan (Wolters Kluwer Medknow Publications, 1999)
A 91/2 year old female born of a nonconsanguineous marriage presented with macrodactyly, hypertrophy of the limb, lymphangioma circumscriptum and varicosities. Lymphangioma circumscriptum was confirmed by histopathology. X-ray of the right foot revealed hypertrophy of both subcutaneous tissue and the underlying bone. This is the second case report from India with the characteristic macrodactyly.